2014
DOI: 10.1002/mabi.201300465
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan‐block‐Poly(ϵ‐Caprolactone) Copolymer Nanoparticles Coated with Chitosan as Biocompatible Mucoadhesive Drug Delivery System

Abstract: The development of novel xyloglucan-block-poly(ϵ-caprolactone) (XGO-b-PCL) nanoparticles coated with the mucoadhesive polysaccharide chitosan is described. XGO-b-PCL nanoparticles show monodisperse size distribution (Rh  = 50 nm). Curcumin is successfully encapsulated within the PCL core within drug to polymer ratio of 1:5 (w/w). The coating of nanoparticles with chitosan results in an increased particle size and positive surface charge due to the polycation nature of the chitosan. Mucoadhesive properties of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…In vitro mucoadhesion study Mazzarino, Coche-Guérente et al (2014), Mazzarino, Otsuka et al (2014) ICL (genipin and sodium salts)…”
Section: Solvent Evaporation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro mucoadhesion study Mazzarino, Coche-Guérente et al (2014), Mazzarino, Otsuka et al (2014) ICL (genipin and sodium salts)…”
Section: Solvent Evaporation Methodsmentioning
confidence: 99%
“…The %EE of curcumin in the NPs was reported to be approximately 99%. Chitosan also creates a positively‐charged surface and strong hydrogen bonds with poloxamer surfactants and consequently, creates highly mucoadhesive nanoparticles (Mazzarino et al, ; Mazzarino, Borsali, & Lemos‐Senna, ; Mazzarino, Coche‐Guérente et al, ; Mazzarino, Otsuka et al, ). These authors indicated that Cur/PCL‐chitosan NPs showed significant toxicity to an SCC‐9 human oral cancer cell line (Mazzarino et al, ).…”
Section: Pharmacological Studies With Curcumin In Chitosan Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano C -ZnPc loaded lipid-core PCL nanocapsules coated with chitosan Nano C was prepared by simple adsorption of chitosan onto Nano B, following the method suggested by Mazzarino et al (2014). Briefly, the adsorption of chitosan was carried out by dropwise addition of a 6.25 mL of chitosan solution (10 mg/mL dissolved in 1% acetic acid) over 17 mL of preformed Nano B.…”
Section: 2mentioning
confidence: 99%
“…Coating of chitosan increases the particle size as well as imparts positive charge, due to its positive surface, to the nanoparticles. The mucoadhesive property of chitosan can be attributed to its exceptional ability to interact with mucin through electrostatic forces (Mazzarino et al, 2014).…”
Section: Special Case Of Microspheres and Nanoparticles As Bioadhesivesmentioning
confidence: 99%